ANALISIS KOMPARATIF SISTEM TANAM MONOKULTUR DAN TANAM TUMPANG SARI JAGUNG DAN KACANG-KACANGAN DI SULAWESI SELATAN - Sari Intang; Amir Amir; Amiruddin Amiruddin (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2021)
Comparative analysis of the feasibility of monoculture maize farming with maize and beans intercropping in South Sulawesi. Optimizing the use of rainfed lowland land in South Sulawesi with corn commodity is still relatively low with a productivity level of 5,49 t/ha. This productivity is still far below the yield potential of superior maize varieties which are at the level of 9-11 t/ha. In the future, the status of agricultural land ownership in Indonesia is relatively narrow due to the population growth rate which has an impact on increasing the conversion of agricultural land for housing and others. encourage farmers to carry out intensification in increasing land productivity, one of which is through planting an intercropping system of corn and beans. This study aims to determine the income comparison between farmers who cultivate corn in monoculture with intercropping of corn and beans. The method of analysis used is the method of financial analysis by calculating the use of costs and income analysis as a consideration for farmers to decide on the selection of technology and innovations that will be adopted in their farming. The results showed that the cost of monoculture corn farming was Rp. 7.200.000, while the intercropping of maize with groundnut, soybean and green beans is Rp. 8.785.000, Rp. 8.015.000, Rp. 8.265.000. The cost of farming in intercropping is higher than the monoculture cropping system, due to the relatively large use of labor in the intercropping system. The income of corn monoculture farmers is 16.737.000 while the income of intercropping beans (peanuts, soybeans and green beans) is Rp. 18.244.000, Rp. 14.860.000, Rp. 16.035.000 The highest intercropping income of corn and peanuts is caused by the high selling price of peanuts compared to the selling prices of other commodities that are simultaneously cultivated, however, in the analysis of the R/C Ratio of corn farming in monoculture the highest (2,32) beat the R/C ratio of peanut intercropping (2,08). This is caused by the use of labor costs in intercropping corn with peanuts which is very high because labor costs in weeding peanuts are done manually. The R/C of soybean intercropping was 1,85 and the R/C of green bean intercropping was 1,94. Keywords: intercropping, income, monoculture, peanut. ABSTRAK Optimalisasi pemanfaatan lahan sawah tadah hujan di Sulawesi Selatan dengan komoditas jagung masih tergolong rendah dengan tingkat produktivitas 5,49 t/ha. Produktivitas tersebut masih jauh dibawah potensi hasil varietas unggul jagung yang berada pada level 9-11 t/ha. Kedepan status kepemilikan lahan pertanian di Indonesia relatif sempit akibat laju pertumbuhan penduduk yang berdampak pada peningkatan alih fungsi lahan pertanian untuk perumahan dan lainnya. Halini yang mendorong petani untuk melakukan intensifikasi dalam meningkatkan produktivitas lahan, yang salah satu caranya melalui penanaman sistem tumpangsari jagung dengan kacang-kacangan. Penelitian ini bertujuan untuk mengetahui perbandingan pendapatan antara petani yang berusahatani jagung secara monokultur dengan tumpangsari jagung dengan kacang-kacangan. Metode analisis yang di lakukan adalah metode analisis finansial dengan menghitung penggunaan biaya-biaya dan analisis pendapatan sebagai bahan pertimbangan petani untuk memutuskan pemilihan teknologi dan inovasi yang akan diadopsi dalam usahataninya. Hasil penelitian menunjukkan bahwa, biaya usahatani jagung secara monokultur sebanyak Rp.7.200.000, sedangkan tumpangsari jagung dengan kacang tanah, kacang kedelai, dan kacang hijau, masing-masinng sebesar Rp.8.785.000, Rp.8.015.000, Rp.8.265.000. Biaya usahatani secara tumpangsari lebih tinggi dibanding dengan sistem tanam monokultur, disebabkan penggunaan tenaga kerja relative banyak pada sistem tumpangsari. Pendapatan petani monokultur jagung Rp.16.737.000,- sedangkan pendapatan tumpangsari kacang-kacangan (kacang tanah, kacang kedelai, dan kacang hijau) masing-masinng sebanyak Rp.18.244.000, Rp.14.860.000, Rp.16.035.000. Pendapatan tumpangsari jagung dan kacang tanah yang paling tinggi disebabkan harga jual kacang tanah tergolong tinggi dibandingkan dengan harga penjualan komoditas lain yang diusahakan secara bersamaan. Namun, pada analisis R/C Ratio usahatani jagung secara monokultur yang paling tinggi (2,32) mengalahkan hasil R/C rasio tumpangsari kacang tanah (2,08). Hal ini disebabkan oleh penggunaan biaya tenaga kerja pada tumpangsari jagung dengan kacang tanah yang sangat tinggi karena biaya tenaga kerja pada penyiangan gulma tanaman kacang tanah di lakukan secara manual. Hasil R/C tumpangsari kacang kedelai 1,85 dan R/C tumpangsari kacang hijau 1,94. Kata Kunci: Tumpangsari, pendapatan, monokultur, kacang tanah.